Метод контроля сварных соединений баллистических сталей с помощью акустической эмиссии - Савченко, Сергей Васильевич; Тимчик, Григорий Семенович (НТУ "ХПИ", 2017)
Рассматривается применение метода акустической эмиссии (АЭ) для контроля сварных соединений баллистических сталей AR. В основе метода лежит физическое явление излучения волн напряжений при быстрой локальной перестройке структуры материала. Исследование проводилось при снятии нагрузки с образца с применением широкополосных акустических пьезодатчиков и новой системой градуировки датчиков АЭ. Была выполнена стыковка системы градуировки с персональным компьютером, разработано специальное программное обеспечение, позволяющее в полуавтоматическом режиме получать амплитудно-частотную характеристику каждого датчика.

The application of the acoustic emission method (AE) for the control of welded joints of ballistic steel AR is considered. The method is based on the physical phenomenon of radiation of stress waves during fast local rearrangement of the material structure. The study was carried out with the removal of the load from the sample using broadband acoustic piezoelectric sensors and a new system for calibrating the AE sensors. The calibration system was mapped to a personal computer, special software was developed that allows the semi-automatic mode to obtain the amplitude-frequency response of each sensor. The use of this method of finding weld defects gives high accuracy and efficiency and allows a tangible reduction in costs and production time. A promising direction is the development of methods for filtering the acoustic signal to increase the accuracy of the method of control.
Method of control of wall compounds of ballistic steels based on acoustic emissions
Keywords: контроль сварных швов; пьезодатчик; неразрушающий контроль; средство защиты; piezoelectric sensor; non-destructive testing; protective equipment